A Review of free fatty acid-induced cell signaling, angiopoietin-like protein 4, and skeletal muscle differentiation - Son, Yura; Paton, Chad M. (Frontiers in Physiology, 2022)
Postnatal skeletal muscle differentiation from quiescent satellite cells is a highly regulated process, although our understanding of the contribution of nutritional factors in myogenesis is limited. Free fatty acids (FFAs) are known to cause detrimental effects to differentiated skeletal muscle cells by increasing oxidative stress which leads to muscle wasting and insulin resistance in skeletal muscle. In addition, FFAs are thought to act as inhibitors of skeletal muscle differentiation. However, the precise molecular mechanisms underlying the effects of FFAs on skeletal muscle differentiation remains to be elucidated. There is a clear relationship between dietary FFAs and their ability to suppress myogenesis and we propose the hypothesis that the FFA-mediated increase in angiopoietin-like protein 4 (ANGPTL4) may play a role in the inhibition of differentiation. This review discusses the role of FFAs in skeletal muscle differentiation to-date and proposes potential mechanisms of FFA-induced ANGPTL4 mediated inhibition of skeletal muscle differentiation.